UPAYA PENINGKATAN KEDISIPLINAN DAN PENERAPAN PROTOKOL KESEHATAN PADA PELAKU WISATA DI SEKITAR WISATA PANTAI PADANG - Shelvy Haria Roza; Ayulia Fardila Sari; Syafrawati Syafrawati (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Tourist destinations are one of the vulnerable places for the spread of Covid-19, as they allow interactions with visitors and food business operators around the tourism locations. Based on data from 2021, it was found that the public's compliance with health protocols in tourist areas in Kota Padang is still low, which poses a risk of increasing Covid-19 cases. Implementing health protocols by following the 5M Movement (maintaining distance, wearing masks, handwashing, avoiding crowds, and reducing travel) at tourist spots such as Pantai Padang is a necessary step for both visitors and business operators in the vicinity of tourist areas to protect themselves and minimize the spread of the Covid-19 pandemic. The purpose of this activity is to educate tourism stakeholders about the importance of implementing health protocols at tourist locations. The implementation method to improve discipline and compliance in the application of health protocols at tourist sites includes conducting location surveys and coordination with partners, educating visitors and tourism stakeholders on health protocol implementation, and conducting evaluations. This activity also provides health promotion materials and distributes masks to visitors and provides handwashing facilities for food business operators. The results of the activity include an increase in participants' knowledge of health protocol implementation in tourist areas, from 13.28 to 13.89, with an average increase of 2.11 points. It is hoped that the Tourism Department will continue to monitor and enhance awareness among tourism stakeholders about the importance of implementing health protocols at tourist destinations.